Lithium battery conductive paste and preparation method thereof
By using a modified melamine resin embedded with lithium and an iron-doped silica film in the conductive paste of lithium batteries, the problem of lithium ion consumption during the first charging process is solved, and the battery's magnification and circulation are improved. Performance extends service life.
Patent Information
- Application Number
- CN202510012466.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-06
AI Technical Summary
During the first charging process of lithium batteries, the organic solvent and lithium salt in the electrolyte undergo a reduction reaction on the surface of the negative electrode, forming an irreversible solid electrolyte interface film, resulting in lithium ion consumption and reducing battery capacity and rate performance.
The modified melamine resin embedded with lithium is added to the lithium battery conductive paste, and an iron-doped silicon dioxide film is formed on the surface, improving electrical conductivity and slowly and stably embedding and removing lithium ions.
It improves the capacitance of lithium batteries, improves the rate performance and cycle performance, and extends the service life of the battery.
Smart Images

Figure CN119400481A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conductive pastes, and more specifically, to a conductive paste for lithium batteries and a preparation method thereof. Background Art
[0002] Lithium battery is an electrochemical energy storage device. Its working process is the process of mutual conversion of electrical energy and chemical energy. It is essentially a concentration difference battery. When charging, the external voltage causes the lithium ions in the positive electrode to escape, flow through the diaphragm through the electrolyte and embed into the negative electrode; when discharging, the lithium ions escape from the negative electrode, flow through the diaphragm through the electrolyte and embed into the positive electrode. The movement of lithium ions inside the battery runs through the charging and discharging process, which has a significant impact on many performances of the battery, such as capacity, rate performance, and cycle life.
[0003] Conductive paste is an important component of lithium batteries and plays an important role in the battery charging and discharging process. Conductive paste forms a stable conductive network between the electrode material particles. When the lithium battery is charged and discharged, it ensures that lithium ions can be quickly embedded in and out of the electrode material, allowing the battery to withstand more charge and discharge cycles while maintaining good performance and extending the battery's cycle life.
[0004] However, lithium batteries still face the problem of unstable rate performance and cycle performance. During the first charging process of lithium batteries, the organic solvent and lithium salt in the electrolyte will undergo a reduction reaction on the surface of the negative electrode. The products generated by these reactions will form a layer of solid electrolyte interface film on the surface of the negative electrode. This reaction is irreversible and will consume a certain amount of lithium ions, reducing the capacity of the lithium battery and further reducing the rate performance of the lithium battery.
[0005] The Chinese patent application document with publication number CN114121384A discloses a water-based conductive slurry and its preparation method and application. The patent application document first prepares nano-mesoporous spheres, then mixes the nano-mesoporous spheres, nitrogen-doped graphene and carbon nanotubes to prepare modified graphene fibers, so that the nano-mesoporous spheres, nitrogen-doped graphene and carbon nanotubes are fixed together on the loose and porous mesh fibers to prepare an efficient conductive fiber mesh structure and form an electrode conductive frame. The successful construction of the conductive fiber mesh structure improves the rate performance and cycle stability of the battery, but fails to effectively solve the problem of lithium battery capacitance reduction caused by the consumption of lithium ions during the first charging of the battery. Summary of the invention
[0006] In order to further improve the rate performance and cycle performance of lithium batteries, the present application provides a lithium battery conductive slurry and a preparation method thereof.
[0007] In a first aspect, the present application provides a lithium battery conductive paste, which adopts the following technical solution: A lithium battery conductive paste comprises the following components in parts by weight: 20-35 parts of graphite, 60-80 parts of carbon black, 1-2 parts of carbon nanotubes, 1-2 parts of graphene, 70-90 parts of a binder, 4-7 parts of polyvinyl pyrrolidone, 15-20 parts of a modified melamine resin, and 650-800 parts of deionized water; The preparation method of the modified melamine resin comprises the following steps: (1) Mix melamine, deionized water and formaldehyde solution evenly, raise the temperature, add sodium hydroxide, react at a constant temperature, and add poloxamer 407 after the reaction to obtain a prepolymer resin; (2) mixing the nano lithium phosphate and the prepolymer resin uniformly, acid curing, crushing, washing, drying and grinding to obtain a lithium embedded melamine resin; (3) Evenly mix ferric chloride, tetraethyl orthosilicate, ethanol and deionized water, acid-catalyze to form gel, replace solvent, add ammonia water to adjust pH, cool, add lithium-intercalated melamine resin, soak, take out the lithium-intercalated melamine resin after soaking, dry, and crush to obtain modified melamine resin.
[0008] By adopting the above technical scheme, a modified melamine resin embedded with lithium is added to the conductive paste of the lithium battery, thereby improving the capacitance of the lithium battery; the iron-doped silica film on the surface of the modified melamine resin improves the conductivity of the modified melamine resin, and enables the lithium ions in the modified melamine resin to be slowly and smoothly embedded and released, thereby improving the rate performance and cycle performance of the lithium battery and extending the service life of the lithium battery.
[0009] Preferably, in step (2), the preparation method of nano lithium phosphate is as follows: after the lithium carbonate solution and phosphoric acid are uniformly mixed, the temperature is increased to react, and after the reaction is completed, the product is washed and dried to obtain nano lithium phosphate.
[0010] By adopting the above technical scheme, the prepared nano lithium phosphate has a good crystal structure and good thermal stability. The crystal structure is not easy to collapse during high-rate charge and discharge, which facilitates the insertion and extraction of lithium ions, making the performance of the lithium battery more stable and improving the rate performance of the lithium battery.
[0011] Preferably, in step (2), the mass ratio of nano lithium phosphate to prepolymer resin is 1:(8-11).
[0012] By adopting the above technical scheme, nano lithium phosphate is evenly dispersed in the prepolymer resin to obtain a lithium-embedded melamine resin with a stable structure. At the same time, during the charging and discharging process, lithium ions can be smoothly embedded in and released from the lithium-embedded melamine resin, thereby improving the charging and discharging efficiency of the battery, thereby improving the rate performance of the lithium battery.
[0013] Preferably, in step (2), the parameters of acid curing are: the pH adjuster is one of hydrochloric acid, phosphoric acid and p-toluenesulfonic acid, the pH value is 2-5, the temperature is 130-150° C., and the time is 20-30 hours.
[0014] By adopting the above technical solution, the cross-linking density of the melamine resin is increased during curing, the molecular chains of the melamine resin can react more fully, a strong network structure is built inside the melamine resin, and the stress caused by the embedding and extraction of lithium ions in the nano-lithium phosphate is effectively dispersed, the lattice distortion of the nano-lithium phosphate is reduced, and the cycle performance of the lithium battery is improved.
[0015] Preferably, in step (3), the mass ratio of ferric chloride, tetraethyl orthosilicate, ethanol and deionized water is 1:(1.8-2.1):(3.5-4):(0.35-0.4).
[0016] By adopting the above technical scheme, the prepared silica sol has good fluidity, which is convenient for forming a uniform film on the surface of the lithium-embedded melamine resin. At the same time, iron ions are introduced into the silica sol, which increases the conductivity of the silica sol, and the iron ions replace part of silicon to enter the network structure. When the film is formed on the surface of the lithium-embedded melamine resin, a uniform pore structure is formed. During the use of the lithium battery, the lithium ions in the modified melamine resin are slowly and smoothly embedded and removed, thereby improving the cycle performance and service life of the lithium battery.
[0017] Preferably, in step (3), the process parameters of acid-catalyzed gelation are as follows: the pH regulator is one of hydrochloric acid and nitric acid, the pH value is 2-4, the temperature is 40-60° C., and the time is 6-8 hours.
[0018] By adopting the above technical scheme, the agglomeration and sedimentation of particles are prevented, the stability of the sol is improved, and the sol can be evenly spread during the film forming process. The surface of the formed film is relatively smooth, so that the film has good mechanical strength and avoids damage due to the internal stress of the lithium battery. During the multiple charge and discharge of the lithium battery, the film still maintains good integrity, extending the service life of the modified melamine resin, thereby improving the cycle performance of the lithium battery.
[0019] Preferably, in step (3), the soaking time is 15-30 seconds.
[0020] By adopting the above technical scheme, the surface film layer of the modified melamine resin has good integrity, and the insertion and extraction of lithium ions in the modified melamine resin are evenly controlled. At the same time, the surface film layer of the modified melamine resin has a smaller thickness, which reduces the hindrance to the movement of lithium ions, thereby improving the rate performance of the lithium battery.
[0021] Preferably, the binder is one of sodium carboxymethyl cellulose, polyvinyl alcohol and polyvinylidene fluoride.
[0022] By adopting the above technical scheme, the long-chain molecular structure of sodium carboxymethyl cellulose, polyvinyl alcohol and polyvinylidene fluoride can be tightly combined with the conductive particles, which helps to establish a good conductive network between the conductive particles, thereby improving the conductivity of the conductive slurry, while making the conductive slurry more stable and less prone to sedimentation or stratification. When used in lithium batteries, the rate performance of lithium batteries is improved.
[0023] In a second aspect, the present application provides a method for preparing a conductive slurry for a lithium battery, comprising the following steps: uniformly mixing graphite, carbon black, carbon nanotubes, graphene, a binder and deionized water, sand-milling, and then adding a modified melamine resin and a dispersant to obtain a conductive slurry for a lithium battery.
[0024] Preferably, the sand milling speed is 1500-2000 rpm and the time is 3-5 hours.
[0025] By adopting the above technical solution, the particle size of the conductive particles is effectively reduced, and the particle agglomeration phenomenon caused by the existence of van der Waals forces between the conductive particles is reduced, so that the dispersion of the conductive particles in the conductive slurry is better, and at the same time the integrity of the conductive particle structure is maintained, avoiding the decrease in the conductive performance of the conductive slurry due to the destruction of the conductive particle structure, so that the conductive slurry has a complete conductive network, the conductivity of the conductive slurry is improved, and the rate performance of the lithium battery is improved.
[0026] In summary, this application has the following beneficial effects: 1. Nano lithium phosphate is embedded in melamine resin. When the lithium battery is working, lithium ions can be extracted and embedded in the modified mesoporous melamine resin. During the charging and discharging process of the lithium battery, the amount of lithium ion embedded and extracted per unit time is increased, which improves the working efficiency of the lithium battery. At the same time, the additional lithium ions introduced into the conductive paste increase the capacitance of the lithium battery. After the nano lithium phosphate is embedded in the modified melamine resin, the lattice structure stability of the nano lithium phosphate that allows lithium ions to be freely embedded and extracted is enhanced, which improves the capacity retention rate of the battery.
[0027] 2. Introducing iron ions into the silica sol improves the conductivity of the silica film and gives the silica film a microporous structure; the silica film is coated on the surface of the lithium-embedded melamine resin, so that the lithium-embedded melamine resin has a certain conductivity and the insertion and removal of lithium ions are slow, avoiding a large amount of lithium ions moving in a short period of time, causing a large amount of heat release inside the battery, destroying the battery structure, and reducing the battery life, thereby improving the battery capacity retention rate and extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the rate performance of lithium batteries assembled with the lithium battery conductive pastes of Examples 1-3 and Comparative Examples 1-2.
[0029] Figure 2It is a schematic diagram of the cycle performance of lithium batteries assembled with the lithium battery conductive pastes of Examples 1-3 and Comparative Examples 1-2.
[0030] Figure 3 It is a particle size distribution diagram of the lithium battery conductive paste of Examples 1-3 and Comparative Examples 1-2.
[0031] Figure 4 This is the state of the slurry after ultrasonic dispersion in the preparation process of the lithium battery conductive slurry in Example 1.
[0032] Figure 5 This is the state of the slurry after sand grinding in the preparation process of the lithium battery conductive slurry in Example 1.
[0033] Figure 6 This is the final state of the lithium battery conductive paste prepared in Example 1. DETAILED DESCRIPTION
[0034] The present application is further described in detail below with reference to the embodiments.
[0035] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0036] Example 1 The conductive paste for lithium batteries of this embodiment is composed of the following components: 20 g of graphite, 60 g of carbon black, 1 g of carbon nanotubes, 1 g of graphene, 70 g of sodium carboxymethyl cellulose, 4 g of polyvinyl pyrrolidone, 15 g of modified melamine resin, and 650 g of deionized water.
[0037] The preparation method of the modified melamine resin of the present embodiment comprises the following steps: (1) 80 g of melamine, 128 g of deionized water, and 184 g of a 37% formaldehyde aqueous solution were added to a 500 mL flask, stirred, and heated to 80°C. 0.16 g of sodium hydroxide was added, reacted for 2 h, cooled to room temperature, and 1.5 g of poloxamer 407 was added and mixed evenly to obtain a prepolymer resin.
[0038] (2) Mix 10 g of nano lithium phosphate and 80 g of prepolymer resin, stir at room temperature, add hydrochloric acid to adjust the pH value of the system to 2, heat to 130 ° C, react for 30 hours, cool to room temperature, crush, wash with 50 ° C ethanol, dry at 60 ° C, and grind to obtain lithium embedded melamine resin.
[0039] (3) Take 20g of ferric chloride, 36g of ethyl orthosilicate, 70g of ethanol and 7g of deionized water and mix them evenly, then add hydrochloric acid to adjust the pH to 2, heat to 40°C, stir and react for 8h, add 150g of deionized water and mix evenly, evaporate at 70°C under reduced pressure for 40min, add ammonia water to adjust the pH to 8, cool to room temperature, add lithium-embedded melamine resin and soak for 15s, then take out the lithium-embedded melamine resin, dry it at 50°C under ventilation for 6h, and crush it to obtain modified melamine resin.
[0040] The preparation method of nano lithium phosphate in this embodiment includes the following steps: 200 mL of an aqueous lithium carbonate solution with a mass percentage concentration of 18% and 200 g of an aqueous phosphoric acid solution with a mass percentage concentration of 15% are mixed evenly, put into a reactor, heated to 190° C., and reacted at a constant temperature for 3 hours. After the reaction is completed, the obtained product is washed and dried at 90° C. for 10 hours to obtain nano lithium phosphate.
[0041] The preparation method of the lithium battery conductive slurry of this embodiment includes the following steps: taking 20g of graphite, 60g of carbon black, 1g of carbon nanotubes, 1g of graphene, 70g of sodium carboxymethyl cellulose, 3g of polyvinyl pyrrolidone, and 650g of deionized water, mixing, ultrasonically dispersing for 20min, and then putting into a vacuum disperser, dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 15m / s, filtering after dispersion, putting the filtrate into a sand mill, sand milling for 5h at a speed of 1500rpm to obtain a mixture, transferring the mixture into a vacuum disperser, adding 15g of modified melamine resin and 1g of polyvinyl pyrrolidone, and dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 20m / s to obtain a lithium battery conductive slurry.
[0042] Example 2 The lithium battery conductive paste of this embodiment is composed of the following components: 35g of graphite, 80g of carbon black, 2g of carbon nanotubes, 2g of graphene, 90g of polyvinyl alcohol, 7g of polyvinyl pyrrolidone, 20g of modified melamine resin, and 800g of deionized water.
[0043] The preparation method of the modified melamine resin of the present embodiment comprises the following steps: (1) 80 g of melamine, 130 g of deionized water, and 180 g of a 37% formaldehyde aqueous solution were added to a 500 mL flask, stirred, and heated to 85°C. Then, 0.15 g of sodium hydroxide was added, reacted for 2 h, cooled to room temperature, and 1.6 g of poloxamer 407 was added and mixed evenly to obtain a prepolymer resin.
[0044] (2) Mix 10 g of nano lithium phosphate and 110 g of prepolymer resin, stir at room temperature, then add phosphoric acid to adjust the pH value of the system to 5, heat to 150°C, react for 20 hours, cool to room temperature, crush, wash with 50°C ethanol, dry at 65°C, and grind to obtain lithium-embedded melamine resin.
[0045] (3) Take 20g of ferric chloride, 42g of ethyl orthosilicate, 80g of ethanol and 8g of deionized water and mix them evenly, then add nitric acid to adjust the pH to 4, heat to 60°C, stir and react for 6h, add 180g of deionized water and mix evenly, evaporate at 70°C under reduced pressure for 50min, add ammonia water to adjust the pH to 9, cool to room temperature, add lithium-embedded melamine resin and soak for 30s, then take out the lithium-embedded melamine resin, dry it at 50°C under ventilation for 6h, and crush it to obtain modified melamine resin.
[0046] The preparation method of nano lithium phosphate of the present embodiment comprises the following steps: 200 mL of lithium carbonate aqueous solution with a mass percentage concentration of 15% and 165 g of phosphoric acid aqueous solution with a mass percentage concentration of 15% are mixed evenly, put into a reactor, heated to 200° C., and reacted at a constant temperature for 3 hours. After the reaction is completed, the obtained product is washed and dried at 100° C. for 10 hours to obtain nano lithium phosphate.
[0047] The preparation method of the lithium battery conductive slurry of this embodiment includes the following steps: 35g of graphite, 80g of carbon black, 2g of carbon nanotubes, 2g of graphene, 90g of polyvinyl alcohol, 5g of polyvinyl pyrrolidone, and 800g of deionized water, ultrasonically disperse for 30min, and then put into a vacuum disperser, disperse for 3h under the conditions of vacuum degree of 0.095MPa, temperature of 15°C, and shear speed of 15m / s, filter after dispersion, put the filtrate into a sand mill, and sand grind for 3h at a speed of 2000rpm to obtain a mixture, transfer the mixture into a vacuum disperser, add 20g of modified melamine resin and 2g of polyvinyl pyrrolidone, and disperse for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 15m / s to obtain a lithium battery conductive slurry.
[0048] Example 3 The conductive paste for lithium batteries of this embodiment is composed of the following components: 25 g of graphite, 70 g of carbon black, 1.5 g of carbon nanotubes, 1.5 g of graphene, 80 g of polyvinylidene fluoride, 6 g of polyvinyl pyrrolidone, 17 g of modified melamine resin, and 690 g of deionized water.
[0049] The preparation method of the modified melamine resin of the present embodiment comprises the following steps: (1) 80 g of melamine, 130 g of deionized water, and 184 g of a 37% formaldehyde aqueous solution were added to a 500 mL flask, stirred, and heated to 80° C. Then, 0.16 g of sodium hydroxide was added, reacted for 2 h, cooled to room temperature, and 1.5 g of poloxamer 407 was added and mixed evenly to obtain a prepolymer resin.
[0050] (2) Mix 10 g of nano lithium phosphate and 90 g of prepolymer resin, stir at room temperature, add p-toluenesulfonic acid to adjust the pH value of the system to 4.5, heat to 135°C, react for 25 hours, cool to room temperature, crush, wash with 50°C ethanol, dry at 60°C, and grind to obtain lithium-embedded melamine resin.
[0051] (3) Take 20g of ferric chloride, 40g of ethyl orthosilicate, 78g of ethanol and 7.5g of deionized water and mix them evenly, then add hydrochloric acid to adjust the pH to 3, heat to 45°C, stir and react for 7h, add 160g of deionized water and mix evenly, evaporate at 70°C under reduced pressure for 45min, add ammonia water to adjust the pH to 8.5, cool to room temperature, add lithium-embedded melamine resin and soak for 20s, then take out the lithium-embedded melamine resin, dry it at 50°C under ventilation for 6h, and crush it to obtain modified melamine resin.
[0052] The preparation method of nano lithium phosphate in this embodiment includes the following steps: 200 mL of an aqueous lithium carbonate solution with a mass percentage concentration of 18% and 200 g of an aqueous phosphoric acid solution with a mass percentage concentration of 15% are mixed evenly, put into a reactor, heated to 190° C., and reacted at a constant temperature for 3 hours. After the reaction is completed, the obtained product is washed and dried at 90° C. for 10 hours to obtain nano lithium phosphate.
[0053] The preparation method of the lithium battery conductive slurry of this embodiment includes the following steps: taking 25g of graphite, 70g of carbon black, 1.5g of carbon nanotubes, 1.5g of graphene, 80g of polyvinylidene fluoride, 5g of polyvinyl pyrrolidone, and 690g of deionized water, mixing, ultrasonically dispersing for 25min, and then putting into a vacuum disperser, dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 12°C, and shear speed of 15m / s, filtering after dispersion, putting the filtrate into a sand mill, sand milling for 4h at a speed of 1800rpm to obtain a mixture, transferring the mixture into a vacuum disperser, adding 17g of modified melamine resin and 1g of polyvinyl pyrrolidone, and dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 20m / s to obtain a lithium battery conductive slurry.
[0054] Comparative Example 1 The lithium battery conductive slurry of this comparative example is composed of the following components: 20g of graphite, 60g of carbon black, 1g of carbon nanotubes, 1g of graphene, 70g of sodium carboxymethyl cellulose, 4g of polyvinyl pyrrolidone, 15g of modified melamine resin, and 650g of deionized water.
[0055] The preparation method of the modified melamine resin of this comparative example comprises the following steps: (1) 80 g of melamine, 128 g of deionized water, and 184 g of a 37% formaldehyde aqueous solution were added to a 500 mL flask, stirred, and heated to 80°C. 0.16 g of sodium hydroxide was added, reacted for 2 h, cooled to room temperature, and 1.5 g of poloxamer 407 was added and mixed evenly to obtain a prepolymer resin.
[0056] (2) Mix 10 g of nano lithium phosphate and 80 g of prepolymer resin, stir at room temperature, add hydrochloric acid to adjust the pH value of the system to 2, heat to 130 ° C, react for 30 hours, cool to room temperature, crush, wash with 50 ° C ethanol, dry at 60 ° C, and grind to obtain modified melamine resin.
[0057] The preparation method of nano lithium phosphate in this comparative example includes the following steps: 200 mL of lithium carbonate aqueous solution with a mass percentage concentration of 18% and 200 g of phosphoric acid aqueous solution with a mass percentage concentration of 15% are mixed evenly, put into a reactor, heated to 190° C., and reacted at a constant temperature for 3 hours. After the reaction is completed, the obtained product is washed and dried at 90° C. for 10 hours to obtain nano lithium phosphate.
[0058] The preparation method of the lithium battery conductive slurry of this comparative example comprises the following steps: taking 20g of graphite, 60g of carbon black, 1g of carbon nanotubes, 1g of graphene, 70g of sodium carboxymethyl cellulose, 3g of polyvinyl pyrrolidone, and 650g of deionized water, mixing, ultrasonically dispersing for 20min, and then putting into a vacuum disperser, dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 15m / s, filtering after dispersion, putting the filtrate into a sand mill, sand milling for 5h at a rotation speed of 1500rpm to obtain a mixture, transferring the mixture into a vacuum disperser, adding 15g of modified melamine resin and 1g of polyvinyl pyrrolidone, and dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 20m / s to obtain a lithium battery conductive slurry.
[0059] Comparative Example 2 The lithium battery conductive slurry of this comparative example is composed of the following components: 20g of graphite, 60g of carbon black, 1g of carbon nanotubes, 1g of graphene, 70g of sodium carboxymethyl cellulose, 4g of polyvinyl pyrrolidone, 15g of nano-lithium phosphate, and 650g of deionized water.
[0060] The preparation method of nano lithium phosphate in this comparative example includes the following steps: 200 mL of lithium carbonate aqueous solution with a mass percentage concentration of 18% and 200 g of phosphoric acid aqueous solution with a mass percentage concentration of 15% are mixed evenly, put into a reactor, heated to 190° C., and reacted at a constant temperature for 3 hours. After the reaction is completed, the obtained product is washed and dried at 90° C. for 10 hours to obtain nano lithium phosphate.
[0061] The preparation method of the lithium battery conductive slurry of this comparative example comprises the following steps: taking 20g of graphite, 60g of carbon black, 1g of carbon nanotubes, 1g of graphene, 70g of sodium carboxymethyl cellulose, 3g of polyvinyl pyrrolidone, and 650g of deionized water, mixing, ultrasonically dispersing for 20min, and then putting into a vacuum disperser, dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 15m / s, filtering after dispersion, putting the filtrate into a sand mill, sand milling for 5h at a rotation speed of 1500rpm to obtain a mixture, transferring the mixture into a vacuum disperser, adding 15g of nano lithium phosphate and 1g of polyvinyl pyrrolidone, and dispersing for 3h under the conditions of vacuum degree of 0.09MPa, temperature of 10°C, and shear speed of 20m / s to obtain a lithium battery conductive slurry.
[0062] Performance testing 1. Preparation of lithium battery: LFP and lithium battery conductive slurry were mixed in a mass ratio of 1:10, and the mixture was coated on aluminum foil after magnetic stirring for 8 hours. The mixture was dried in a dryer at 80°C for 12 hours to obtain carbon-coated foil. The carbon-coated foil was cut into small discs with a diameter of 14 mm using a puncher, and the discs were kept at a pressure of 0.6 MPa for 30 seconds. The carbon-coated foil was then placed in a vacuum drying oven at 120°C and dried for 12 hours to obtain a working electrode. The working electrode was then weighed in a glove box, and a CR2016 button cell was assembled using a Celegard 2400 membrane as a diaphragm, a metal lithium foil as a counter electrode, and a LiPF6 solution with a molar concentration of 1 mol / L as an electrolyte. The solvent of the LiPF6 solution was a mixture of ethylene carbonate, dimethyl carbonate, and diethyl carbonate, and their volume ratio was 1:1:1. The assembly process of the lithium battery is carried out in a sealed argon-filled glove box. The moisture and oxygen content in the glove box are kept within 1ppm, and the mass of the active material in the working electrode is about 3mg.
[0063] 2. The cycle performance test of lithium batteries is carried out under the conditions of charging current density of 1C and discharging current density of 2C.
[0064] 3. Use a laser particle size distribution analyzer to test the particle size distribution of the lithium battery conductive slurry of Examples 1-3 and Comparative Examples 1-2 to obtain a particle size distribution diagram, such as Figure 3 shown.
[0065] 4. During the preparation of the lithium battery conductive slurry of Example 1, the appearance of the slurry was observed, and it can be observed that the slurry was gradually dispersed evenly, such as Figure 4 , Figure 5 and Figure 6 shown.
[0066] Analyze Examples 1-3 and Comparative Examples 1-2 and combine Figure 1 and Figure 2 It can be seen that the lithium battery prepared by adding the modified melamine resin into the lithium battery conductive paste has good rate performance and cycle performance.
[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lithium battery conductive paste, characterized in that: The invention comprises the following components in parts by weight: 20-35 parts of graphite, 60-80 parts of carbon black, 1-2 parts of carbon nanotubes, 1-2 parts of graphene, 70-90 parts of a binder, 4-7 parts of polyvinyl pyrrolidone, 15-20 parts of a modified melamine resin, and 650-800 parts of deionized water; The preparation method of the modified melamine resin comprises the following steps: (1) Mix melamine, deionized water and formaldehyde solution evenly, raise the temperature, add sodium hydroxide, react at a constant temperature, and add poloxamer 407 after the reaction to obtain a prepolymer resin; (2) mixing the nano lithium phosphate and the prepolymer resin uniformly, acid curing, crushing, washing, drying and grinding to obtain a lithium embedded melamine resin; (3) Evenly mix ferric chloride, tetraethyl orthosilicate, ethanol and deionized water, acid-catalyze to form gel, replace solvent, add ammonia water to adjust pH, cool, add lithium-intercalated melamine resin, soak, take out the lithium-intercalated melamine resin after soaking, dry, and crush to obtain modified melamine resin.
2. The conductive paste for lithium batteries according to claim 1, characterized in that: In the step (2), the preparation method of nano lithium phosphate comprises the following steps: mixing lithium carbonate solution and phosphoric acid evenly, heating to react, and after the reaction is completed, washing and drying the product to obtain nano lithium phosphate.
3. The conductive paste for lithium battery according to claim 1, characterized in that: In the step (2), the mass ratio of nano lithium phosphate to prepolymer resin is 1:(8-11).
4. The conductive paste for lithium batteries according to claim 1, characterized in that: In the step (2), the process parameters of acid curing are: the pH adjuster is one of hydrochloric acid, phosphoric acid and p-toluenesulfonic acid, the pH value is 2-5, the temperature is 130-150°C, and the time is 20-30h.
5. The conductive paste for lithium batteries according to claim 1, characterized in that: In the step (3), the mass ratio of ferric chloride, tetraethyl orthosilicate, ethanol and deionized water is 1:(1.8-2.1):(3.5-4):(0.35-0.4).
6. The conductive paste for lithium batteries according to claim 1, characterized in that: In the step (3), the process parameters of acid-catalyzed gelation are: the pH regulator is hydrochloric acid or nitric acid, the pH value is 2-4, the temperature is 40-60°C, and the time is 6-8h.
7. The conductive paste for lithium batteries according to claim 1, characterized in that: In the step (3), the soaking time is 15-30 seconds.
8. The conductive paste for lithium batteries according to claim 1, characterized in that: The binder is one of sodium carboxymethyl cellulose, polyvinyl alcohol and polyvinylidene fluoride.
9. A method for preparing a lithium battery conductive paste as claimed in claim 1, characterized in that: The method comprises the following steps: mixing graphite, carbon black, carbon nanotubes, graphene, a binder and deionized water uniformly, sand-milling, and then adding a modified melamine resin and a dispersant to obtain a lithium battery conductive slurry.
10. The method for preparing a lithium battery conductive paste according to claim 9, characterized in that: The sand mill has a rotation speed of 1500-2000 rpm and a time of 3-5 hours.
Citation Information
Patent Citations
Special graphene conductive paste for lithium-ion battery and preparation method thereof
CN109950541A
Nitrogen-doped porous hollow carbon sphere and preparation method and application thereof
CN110729480A
Water-based conductive paste and preparation method and application thereof
CN114121384A
Lithium iron phosphate positive electrode material, preparation method and lithium ion battery
CN115863576A
Conductive paste containing halloysite, carbon-coated foil and preparation method and application of conductive paste
CN116435004A